Validitas E-Modul Pembelajaran Berbasis Problem Based Learning Terintegrasi Curipod untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik pada Materi Sistem Ekskresi - Ilham Mahajani; Djuna Lamondo; Nur Mustaqimah; Margaretha Solang; Lilan Dama (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to develop and test the validity of Curipod's integrated Problem Based Learning (PBL) based learning e-Module on excretory system material as biology teaching material at SMA Negeri 1 Suwawa. This research is a type of research and development or Research and Development (R&D) with the ADDIE model which includes Analysis, Design, Develop, Implement and Evaluate. However, this research only reached the stage of development and limited scale trials. The data collection instruments used consisted of validation sheets of media experts and material experts. The results of the study show that the Curipod integrated PBL-based learning e-Module is in the very valid category, with a percentage of media expert validity of 95% and validity of material expert of 97%. Thus, these findings show that the developed E-Module is suitable for use as teaching materials to support biology learning in excretory system materials.